Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Pada Pengguna Aplikasi Jasa Gojek di Bekasi - Winaya Purwanti; Asep Saifudin; Henny Risnawati (LPPM Swadaya Institute of Business and Communication, 2022)
This study aims to determine and analyze the factors that influence consumer satisfaction with Gojek service application users in Bekasi. The factors studied were service quality, price, brand image, and promotion factors. The approach used in this research is associative by using primary data through questionnaires and interviews. The population in this study are consumers in the city of Bekasi who have the Gojek application on their cell phones and have used it at least 5 times. The sampling method used probability sampling with a sample of 100 people. The data analysis technique used multiple linear regression, partial, and simultaneous hypothesis testing, and looking for the coefficient of determination. The results of the study stated that the factors of service quality, price, brand image, and promotion had a positive and significant influence on consumer satisfaction for Gojek service application users in Bekasi either partially or simultaneously.